Reductive catalytic fractionation: state of the art of the lignin-first biorefinery. (April 2019) - Renders, Tom; Van den Bossche, Gil; Vangeel, Thijs; Van Aelst, Korneel; Sels, Bert
Highlights: Reductive catalytic fractionation yields a low- Mw lignin oil and carbohydrate pulp. Elementary steps are (i) solvolytic lignin extraction, (ii) depolymerisation and (iii) catalytic stabilisation. Flow-through RCF decouples extraction from catalysis and is a semi-continuous process. The feedstock spectrum ranges from low-value waste streams to high-value bioengineered crops. The multidisciplinary nature of biorefining asks for joint research efforts across different disciplines. Abstract : Reductive catalytic fractionation (RCF) of lignocellulose is an emerging biorefinery scheme that combines biomass fractionation with lignin depolymerisation. Central to this scheme is the integration of heterogeneous catalysis, which overcomes the tendency of lignin to repolymerise. Ultimately, this leads to a low- Mw lignin oil comprising a handful of lignin-derived monophenolics in close-to-theoretical yield, as well as a carbohydrate pulp. Both product streams are considered to be valuable resources for the bio-based chemical industry. This Opinion article sheds light on recently achieved milestones and consequent research opportunities. More specifically, mechanistic studies have established a general understanding of the elementary RCF steps, which include (i) lignin extraction, (ii) solvolytic and catalytic depolymerisation and (iii) stabilisation. This insight forms the foundation for recently developed flow-through RCF. Compared to traditional batch, flow-through RCF has the advantage of (i) separating the solvolytic steps from the catalytic steps and (ii) being a semi-continuous process; both of which are beneficial for research purposes and for industrial operation. Although RCF has originally been developed for 'virgin' biomass, researchers have just begun to explore alternative feedstocks. Low-value biomass sources such as agricultural residues, waste wood and bark, are cheap and abundant but are also often more complex. On the other side of the feedstock spectrum are high-value bio-engineered crops, specifically tailored for biorefinery purposes. Advantageous for RCF are feedstocks designed to (i) increase the total monomer yield, (ii) extract lignin more easily, and/or (iii) yield unconventional, high-value products (e.g. alkylated catechols derived from C-lignin). Taking a look at the bigger picture, this Opinion article highlights the multidisciplinary nature of RCF. Collaborative efforts involving chemists, reactor engineers, bioengineers and biologists working closer together are, therefore, strongly encouraged.